Pars Plana Vitrectomy following Traumatic Ocular Injury and Initial Globe Repair: A Retrospective Analysis of Clinical Outcomes. (25th January 2021) - Phillips, Hunter H; Blegen IV, Halward J; Anthony, Christopher; Davies, Brett W; Wedel, Marissa L; Reed, Donovan S
ABSTRACT: Introduction: Penetrating and perforating ocular trauma are often devastating and may lead to complete visual loss in the traumatized eye and subsequent compromise of the fellow eye. A significant proportion of traumatic injuries are complex, often requiring vitreoretinal intervention to preserve vision. A retrospective analysis at a level 1 trauma center was performed to evaluate the time course, incidence, and outcomes following pars plana vitrectomy (PPV) after traumatic ocular injury and initial globe repair. Materials and Methods: Eyes that underwent open globe repair following ocular trauma at Brooke Army Medical Center, between January 1, 2014 and December 30, 2016 were analyzed. Specific factors evaluated include mechanism of injury, defect size and complexity, ocular trauma score, zone of injury, associated orbital trauma, and time from injury to surgical intervention. A subset analysis was conducted specifically on eyes requiring subsequent PPV for vision preservation because of vitreoretinal disease. Surgical outcomes, time to secondary intervention, and complication rates were then assessed. Results: In total, 70 eyes requiring open globe repair were examined, with 43 having undergone PPV. Average and median time to vitrectomy were 18.8 and 8 days, respectively. Eyes that underwent PPV were more likely to have an afferent papillary defect, vitreous hemorrhage, intraocular foreign body, and retinal detachment at the time of initial injury (although the latter two factors were not statistically significant), and were more likely to receive penetrating keratoplasty. Proliferative vitreoretinopathy occurred in 37.2% of eyes that underwent PPV, versus 3.7% of those that did not ( P = 0.0013). Timing of PPV (i.e., before or after 14 days) had no statistically significant effect on the rate of PVR (Table I ). Eyes that underwent PPV showed an improvement of visual acuity from average 2.5 logMAR following initial injury to 1.5 logMAR 6 months after PPV, equivalent to 18.7 Early Treatment Diabetic Retinopathy Study (ETDRS) letters gained, versus 37.7 ETDRS letters gained in eyes without PPV. Among PPV eyes, early repair (<14 days) was associated with greater improvement in visual acuity. Conclusion: Overall, patients requiring PPV following open globe repair generally had more severe injuries and worse 6-month postoperative visual acuity. Patients who underwent more expedited vitrectomy showed greater improvement in visual acuity as measured by ETDRS letters gained.